Electromagnetic shielding fabric and preparation method thereof
By using ferrite/graphene gel solution and polyimide spinning liquid doped with bismuth ions, the problems of high production costs and complex structure in the prior art are solved, and good electromagnetic shielding and breathability are achieved.
Patent Information
- Application Number
- CN202411903144.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
AI Technical Summary
The production cost of existing electromagnetic shielding fabrics is relatively high and the structure is complex, making it difficult to effectively solve the problem of electromagnetic radiation pollution.
The ferrite/graphene gel solution is used as the internal phase spinning liquid and the polyimide spinning liquid doped with bismuth ions is used as the external phase spinning liquid. The gel fibers with core-shell structure are prepared by spinning, and a metal bismuth layer is formed under the reduction of sodium borohydride to enhance electromagnetic shielding performance.
It achieves good electromagnetic shielding effect, while improving the breathable performance of the fabric and reducing production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, and in particular to an electromagnetic shielding fabric and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology and the improvement of people's living standards, the types and numbers of various electronic devices and household appliances are also increasing. While modern scientific and technological progress provides various conveniences for human life, it also brings many potential hazards. An invisible and intangible pollution source is increasingly attracting attention from all walks of life at home and abroad. This is electromagnetic radiation, which is called the "invisible killer". For the human body, a good conductor, electromagnetic waves will inevitably cause a certain degree of harm. Relevant studies have shown that electromagnetic waves with a frequency of more than 150MHz will have a serious impact on human health. Electromagnetic radiation will not only cause dysfunction of the human central nervous system and autonomic nervous system disorders mainly with sympathetic fatigue and tension, causing neurasthenia, but also may cause gene mutations in human cells, causing cell cancer, miscarriage in pregnant women, fetal malformations and other lesions. The problem of electromagnetic radiation pollution has become the fourth largest source of pollution after water pollution, air pollution and solid waste pollution. Since electromagnetic radiation is widely present in people's living and working environment and is becoming increasingly serious, it has attracted people's attention, so the means, methods and materials for protecting electromagnetic radiation have come into being.
[0003] At present, the most commonly used radiation protection method in the world is to wear radiation protection clothing. The fibers used to make radiation protection clothing mainly include the following types: 1) radiation-resistant fibers, which are radiation-resistant in themselves; 2) composite radiation-resistant fibers, which are made radiation-resistant by adding other compounds or elements to the fibers; 3) conductive absorbing fibers, which rely on the reflection of electromagnetic radiation by low-resistance conductive materials to generate current and magnetic polarization opposite to the original electromagnetic radiation in the conductor, forming a shielding space, thereby reducing the harm of external electromagnetic radiation.
[0004] Patent CN103465526A discloses a flexible electromagnetic shielding composite material, which includes a surface layer and a conductive fiber shielding layer, wherein the conductive fiber shielding layer includes a base fabric and a conductive fiber layer, wherein the conductive fiber shielding layer is made by regularly laying conductive fiber filament bundles on the base fabric in an equidistant manner; the composite material is obtained by overlapping the above composite material with a certain overlap angle and a certain number of overlapping layers. Although the electromagnetic shielding performance of the composite material prepared by this patent has been significantly improved, and it has the characteristics of low cost, wide bandwidth, and high performance. However, the composite material is obtained by overlapping each other with a certain overlap angle and a certain number of overlapping layers, and the structure is too complicated, the conductive fiber consumption is large, and the production cost is high. Summary of the invention
[0005] The object of the present invention is to provide an electromagnetic shielding fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing an electromagnetic shielding fabric, characterized in that it comprises the following preparation steps: (1) spinning with a ferrite / graphene gel solution as an inner phase spinning solution and a polyimide spinning solution doped with bismuth ions as an outer phase spinning solution, wherein the mass ratio of the polyimide spinning solution to bismuth nitrate in the polyimide spinning solution doped with bismuth ions is 10:1-3, and then pre-treating to obtain a fiber precursor; (2) Mix the fiber precursor, deionized water, and sodium borohydride, react at 40-50°C for 8 hours, take out, dry at 80-100°C for 24 hours, heat to 150-260°C, and dry for 5 hours to obtain the homemade polyimide fiber; (3) blending and weaving homemade polyimide fiber, polyurethane elastic fiber and polyester fiber to obtain fabric; (4) The fabric, cuprous chloride, acetonitrile, triethylamine, and diethyl iodophenyl were mixed, ultrasonically oscillated at 400-500 W for 1 h, taken out, and dried at 40° C. for 12 h to obtain an electromagnetic shielding fabric.
[0007] Furthermore, the preparation method of the polyimide spinning solution is: using solvent A to dissolve diamine, and then adding dianhydride thereto at a molar ratio of dianhydride to diamine of (0.9-1.1):1, the total amount of dianhydride and diamine makes the solid content of the polyamic acid solution be 15-30%, the temperature is 10-50°C, the reaction is 8-20h, and the polyamic acid spinning solution I is obtained, the apparent viscosity of which is 50000-300000cp, and after filtration, vacuum degassing is carried out for 8-15h.
[0008] Furthermore, the solvent A is selected from one or more of dimethylacetamide, dimethylformamide, N,N-dimethylpyrrolidone, dimethyl sulfoxide, and tetrahydrofuran.
[0009] Furthermore, the dianhydride is selected from one or more of phthalic anhydride, biphenyl dianhydride, triphenyl diether dianhydride, diphenyl ether dianhydride, benzophenone dianhydride, and bisphenol A diether dianhydride.
[0010] Furthermore, the diamine is selected from one or more of 4,4'-diaminodiphenyl ether diamine, p-phenylenediamine, diphenyl diether diamine, and bisphenol A type diether diamine.
[0011] Furthermore, the specific steps of the pretreatment in step (1) are: drying at 100-120°C for 30 minutes, heating to 150-300°C, and drying for 4 hours.
[0012] Furthermore, the preparation method of the ferrite / graphene gel solution in step (1) is as follows: dispersing graphene oxide in deionized water with a mass of 1000 times that of graphene oxide, ultrasonically dispersing at 500-600W for 1 hour, adding sodium hydroxide with a mass of 10 times that of graphene oxide, continuing ultrasonication for 30 minutes, adding bromoacetic acid with a mass of 20 times that of graphene oxide, continuing ultrasonication for 15 minutes, reacting for 4-5 hours, centrifuging at 5000-6000rpm for 10 minutes, filtering, and vacuuming to - 0.08MPa, 60℃ drying for 10h to obtain pretreated graphene; pretreated graphene, deionized water, ferric chloride, barium nitrate and anhydrous ethanol are mixed in a mass ratio of 1:100:6:0.8:394~1:100:8:1.0:394, ultrasonically react at 80℃ and 500~600W for 30min, add ammonia water until the solution pH is 8, then add hydrazine hydrate 2~3 times the mass of the pretreated graphene, and continue ultrasonication for 6~7h to obtain a ferrite / graphene gel solution.
[0013] Furthermore, the spinning process conditions of step (1) are: voltage of 20 kV, receiving distance of 20 cm, temperature of 35° C., humidity of 40%, external phase flow rate of 0.4 mm / min, and internal phase flow rate of 0.2 mm / min.
[0014] Furthermore, in step (2), the mass ratio of the fiber precursor, deionized water, and sodium borohydride is 1:20:1 to 1:60:4.
[0015] Furthermore, in step (3), the mass ratio of the self-made polyimide fiber, polyurethane elastic fiber and polyester fiber is 1:1:0.5~3:1:2.
[0016] Furthermore, the weight of the fabric in step (3) is 140-180 g / m 2 .
[0017] Furthermore, in step (4), the mass ratio of the fabric, cuprous chloride, acetonitrile, triethylamine and diethyl iodophenyl is 1:0.1:10:1:1.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention uses polyimide doped with bismuth ions as an external spinning solution. The polyimide contains a large number of benzene ring structures and has a certain electromagnetic shielding effect. After being subjected to high-energy radiation, no radiation crosslinking and chemical degradation reactions are generated, and the fabric has a good electromagnetic shielding effect. Then, the carboxylated graphene oxide generates electrostatic adsorption with barium ions and iron ions, so that ferrite is loaded on the graphene sheet layer, generating a synergistic shielding effect, and improving the electromagnetic shielding effect of the fabric. The core-shell structured gel fiber is spun using the core-shell structured gel fiber as an internal phase and the polyimide as an external phase, and a double-layer electromagnetic wave absorption path is constructed. Then, under the reduction action of sodium borohydride, a uniform layer of metal bismuth is formed on the fiber surface, thereby enhancing the electromagnetic shielding performance of the fabric. After drying, the inner layer of gel forms a porous aerogel structure, and the holes of the aerogel structure are connected with the pores of the fiber, thereby improving the air permeability of the fabric. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the electromagnetic shielding fabrics prepared in the following examples are as follows: Electromagnetic shielding: The shielding effectiveness of the embodiment and the comparative example of the same size was tested with reference to SJ20524, and the test was carried out using a FY800 fabric electromagnetic radiation protection performance tester and a network analyzer at 20°C and a relative humidity of 50%. Example 1
[0021] (1) Dissolving 4,4'-diaminodiphenyl ether diamine in dimethylformamide, and then adding phthalic anhydride in a molar ratio of phthalic anhydride to 4,4'-diaminodiphenyl ether diamine of 0.9:1, reacting at 35°C for 14 hours to obtain polyamic acid spinning solution I, filtering and vacuum degassing for 10 hours to obtain polyimide spinning solution; (2) Disperse graphene oxide in deionized water with a mass of 1000 times that of graphene oxide, ultrasonically disperse at 600W for 1h, then add sodium hydroxide with a mass of 10 times that of graphene oxide, continue ultrasonication for 30min, then add bromoacetic acid with a mass of 20 times that of graphene oxide, continue ultrasonication for 15min, react for 5h, centrifuge at 6000rpm for 10min, filter, and dry at 60℃ for 10h under vacuum degree of -0.08MPa to obtain pretreated graphene; mix pretreated graphene, deionized water, ferric chloride, barium nitrate, and anhydrous ethanol in a mass ratio of 1:100:6:0.8:394, ultrasonically react at 80℃ and 600W for 30min, then add ammonia water until the solution has a pH of 8, then add hydrazine hydrate with a mass of 3 times that of the pretreated graphene, continue ultrasonication for 6~7h to obtain a ferrite / graphene gel solution; (3) Spinning was performed using a ferrite / graphene gel solution as the inner phase spinning solution and a bismuth ion-doped polyimide spinning solution as the outer phase spinning solution. The spinning process conditions were: voltage of 20 kV, receiving distance of 20 cm, temperature of 35 ° C, humidity of 40%, outer phase flow rate of 0.4 mm / min, inner phase flow rate of 0.2 mm / min, and the mass ratio of polyimide spinning solution to bismuth nitrate in the bismuth ion-doped polyimide spinning solution was 10:1. After drying at 110 ° C for 30 min, the temperature was raised to 260 ° C and dried for 4 h to obtain a fiber precursor. (4) The fiber precursor, deionized water, and sodium borohydride were mixed in a mass ratio of 1:35:2.5, reacted at 50°C for 8 hours, taken out, dried at 100°C for 24 hours, heated to 260°C, and dried for 5 hours to obtain the homemade polyimide fiber; (5) Self-made polyimide fiber, polyurethane elastic fiber and polyester fiber are blended in a mass ratio of 3:1:2 and woven to obtain a gram weight of 180 g / m 2 Fabrics; (6) The fabric, cuprous chloride, acetonitrile, triethylamine, and diethyl iodophenyl were mixed in a mass ratio of 1:0.1:10:1:1, ultrasonically oscillated at 500 W for 1 h, taken out, and dried at 40 ° C for 12 h to obtain an electromagnetic shielding fabric. Example 2
[0022] The difference between Example 2 and Example 1 is that the mass ratio of pretreated graphene, deionized water, ferric chloride, barium nitrate, and anhydrous ethanol is 1:100:7:0.9:394, and the remaining components and steps are the same as Example 1. Example 3
[0023] The difference between Example 3 and Example 1 is that the mass ratio of pretreated graphene, deionized water, ferric chloride, barium nitrate, and anhydrous ethanol is 1:100:8:1.0:394, and the other components and steps are the same as Example 1. Example 4
[0024] The difference between Example 4 and Example 1 is that the mass ratio of polyimide spinning solution to bismuth nitrate in the polyimide spinning solution doped with bismuth ions is 10:2, and the other components and steps are the same as those in Example 1. Example 5
[0025] The difference between Example 5 and Example 1 is that the mass ratio of polyimide spinning solution and bismuth nitrate in the polyimide spinning solution doped with bismuth ions is 10:3, and the other components and steps are the same as those in Example 1. Example 6
[0026] The difference between Example 6 and Example 1 is that the dianhydride is biphenyl dianhydride, the diamine is diphenyl diether diamine, the molar ratio of dianhydride to diamine is 1.0:1, and the other components and steps are the same as in Example 1. Example 7
[0027] The difference between Example 7 and Example 1 is that the dianhydride is bisphenol A type diether dianhydride, the diamine is bisphenol A type diether diamine, the molar ratio of dianhydride to diamine is 1.0:1, and the other components and steps are the same as in Example 1. Example 8
[0028] The difference between Example 8 and Example 1 is that the dianhydride is benzophenone dianhydride, the diamine is diphenyl diether diamine, the molar ratio of dianhydride to diamine is 1.1:1, and the other components and steps are the same as in Example 1.
[0029] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that bismuth nitrate is not added, and the remaining steps are the same as those of Example 1.
[0030] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step (4) is not performed, and the remaining steps are the same as those of Example 1.
[0031] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that there is no step (2), and step (3) is changed to: polyimide spinning solution, bismuth nitrate and ferric chloride are mixed in a mass ratio of 10:1:1 to obtain a spinning solution, spinning is carried out, and then drying is carried out at 110°C for 30 minutes, heating to 260°C, and drying for 4 hours to obtain a fiber precursor. The remaining steps are the same as those in Example 1.
[0032] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that there is no step (2), and step (3) is changed to: polyimide spinning solution, bismuth nitrate and graphene oxide are mixed in a mass ratio of 10:1:1 to obtain a spinning solution, spinning is carried out, and then drying is carried out at 110°C for 30 minutes, heating to 260°C, and drying for 4 hours to obtain a fiber precursor. The remaining steps are the same as those in Example 1.
[0033] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that step (3) is different. Step (3) is changed to: polyimide spinning solution, bismuth nitrate, and ferrite / graphene gel solution are mixed in a mass ratio of 10:1:1, and spinning is carried out. Then, after drying at 110°C for 30 minutes, the temperature is increased to 260°C and dried for 4 hours to obtain a fiber precursor. The remaining steps are the same as Example 1.
[0034] Effect example Table 1 below shows the performance analysis results of the electromagnetic shielding fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0035] Table 1
[0036] From the comparison of the experimental data of the antibacterial rate of the embodiment and the comparative example, it can be found that the present invention uses polyimide doped with bismuth ions as the external phase spinning solution, and the polyimide contains a large number of benzene ring structures, which has a certain shielding effect on electromagnetics. After being subjected to high-energy radiation, no radiation crosslinking and chemical degradation reactions occur, and it has a good electromagnetic shielding effect; then, the carboxylated graphene oxide produces electrostatic adsorption with barium ions and iron ions, so that the ferrite is loaded on the graphene sheet, resulting in a synergistic shielding effect, thereby improving the electromagnetic shielding effect of the fabric, and using this as the inner phase and polyimide as the outer phase, spinning to obtain a core-shell structured gel fiber, constructing a double-layer electromagnetic wave absorption path, and then under the reduction action of sodium borohydride, a uniform layer of metal bismuth is formed on the fiber surface, thereby enhancing the electromagnetic shielding performance of the fabric, and then through drying, the inner layer of the gel forms a porous aerogel structure, the holes of which are connected with the pores of the fiber, thereby improving the air permeability of the fabric.
[0037] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing an electromagnetic shielding fabric, characterized in that: The method comprises the following preparation steps: (1) spinning with a ferrite / graphene gel solution as an inner phase spinning solution and a polyimide spinning solution doped with bismuth ions as an outer phase spinning solution, wherein the mass ratio of the polyimide spinning solution to bismuth nitrate in the polyimide spinning solution doped with bismuth ions is 10:1-3, and then pre-treating to obtain a fiber precursor; (2) Mix the fiber precursor, deionized water, and sodium borohydride, react at 40-50°C for 8 hours, take out, dry at 80-100°C for 24 hours, heat to 150-260°C, and dry for 5 hours to obtain the homemade polyimide fiber; (3) blending and weaving homemade polyimide fiber, polyurethane elastic fiber and polyester fiber to obtain fabric; (4) The fabric, cuprous chloride, acetonitrile, triethylamine, and diethyl iodophenyl were mixed, ultrasonically oscillated at 400-500 W for 1 h, taken out, and dried at 40° C. for 12 h to obtain an electromagnetic shielding fabric.
2. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: The specific steps of the pretreatment in step (1) are: drying at 100-120°C for 30 minutes, heating to 150-300°C, and drying for 4 hours.
3. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: The spinning process conditions of step (1) are: voltage of 20 kV, receiving distance of 20 cm, temperature of 35° C., humidity of 40%, external phase flow rate of 0.4 mm / min, and internal phase flow rate of 0.2 mm / min.
4. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: In step (2), the mass ratio of the fiber precursor, deionized water and sodium borohydride is 1:20:1 to 1:60:
4.
5. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: The mass ratio of the self-made polyimide fiber, polyurethane elastic fiber and polyester fiber in step (3) is 1:1:0.5~3:1:
2.
6. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: The weight of the fabric in step (3) is 140-180 g / m 2 .
7. The method for preparing an electromagnetic shielding fabric according to claim 1, characterized in that: The mass ratio of the fabric, cuprous chloride, acetonitrile, triethylamine and diethyl iodophenyl in step (4) is 1:0.1:10:1:
1.
8. An electromagnetic shielding fabric, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Flexible electromagnetic screen composite material
CN103465526A
Cited By
Anti-radiation fiber as well as preparation method and application thereof
CN120330906A
Radiation resistant fiber and method of making and use thereof
CN120330906B